Furoshiki : the Japanese art of wrapping with fabric - Le Marec, Aurélie (Search Press, 2022)
Furoshiki is a traditional Japanese wrapping cloth, and is used to wrap gifts and create bags for carrying things more easily. Once you have learned the basic methods of tying and folding, you can tie furoshiki in different ways to suit the size and shape of the contents within. There is no sewing involved and, using just a square of fabric, Aurélie Le Marec shows you how to wrap all kinds of items from books to guitars and laptops to wine bottles. You can adapt furoshiki to suit items of all shapes and sizes and, with more than 50 furoshiki folds explained with step-by-step illustrations and clear instructions, you can help to reduce waste by making furoshiki part of your everyday life.